SpaceOAR Hydrogel in Dose-escalated Prostate Cancer Radiotherapy: Rectal Dosimetry and Late Toxicity. Issue 10 (October 2016) - Whalley, D.; Hruby, G.; Alfieri, F.; Kneebone, A.; Eade, T.
Abstract: Aim: To investigate the feasibility, dosimetric benefits and late toxicity of a temporary hydrogel spacer between the rectum and the prostate for prostate intensity-modulated radiotherapy. Materials and methods: Thirty patients with prostate cancer were enrolled on a phase I/II study. All patients underwent magnetic resonance imaging before and after placement of 10 cm 3 of hydrogel. The first 10 patients had an additional magnetic resonance imaging after the completion of radiation treatment. SpaceOAR hydrogel was injected under general anaesthetic using a transperineal approach with transrectal ultrasound guidance. Primary end points were perioperative toxicity and comparison of rectal dosimetry. Secondary end points included cute and late radiation toxicity. All patients were planned on both pre- and post-hydrogel scans to a D95 of 80 Gy in 40 fractions. A contemporary control group of 110 prostate cancer patients treated with the same prescription was identified for comparison. Results: There were no perioperative complications. Rectal doses were significantly lower for the post-hydrogel plans, especially above 65 Gy (V82 = 0.2% versus 1.3%; V80 = 0.8% versus 5.3%; V75 = 2.2% versus 9.5%; V70 = 3.7% versus 12.3%; V65 = 5.4% versus 14.7%; V40 = 22.9% versus 32% and V30 = 42.7% versus 49.4%). There was no significant difference in acute grade 1 and 2 gastrointestinal toxicity, which was 43% versus 51% and 0% versus 4.5% in the hydrogel and control groups, respectively. Late grade 1 was significantly less frequent in the hydrogel group (16.6% versus 41.8%, P  = 0.04). Conclusion: SpaceOAR hydrogel was inserted with minimal side-effects. Dosimetric benefits were greatest at higher rectal doses (V65 to V82). Late grade 1 gastrointestinal toxicity was significantly lower than that seen in patients treated without hydrogel. Highlights: 30 patients with prostate cancer were treated with hydrogel in situ on a prospective trial. Patients received 80 Gy in 40 fractions using an IMRT technique. Plans pre- and post-hydrogel insertion showed significant reductions in rectal doses with hydrogel. Patients had a minimum follow-up of 2 years (median = 28 months). Late grade 1 rectal toxicity was reduced in the hydrogel group compared to a cohort treated without.